Pemeriksaan Kesehatan Lansia dan Senam Lansia di Desa Karta Dewa Kabupaten Penukal Abab Lematang Ilir Tahun 2025 - Alkhusari Alkhusari; Amien Saputra; Azka Ryanita; Azzahra Abshary Myrandha (JURNAL PENGABDIAN KADER BANGSA, 2026)
The elderly is a development of government policies through health services for the elderly which are implemented through the Posyandu program by involving the participation of the elderly, families, community leaders and social organizations in its implementation. The purpose of this activity is to improve the quality of life of the elderly through periodic health checks and structured elderly gymnastics programs. Methods: This community service activity includes basic health checks (blood pressure, and simple physical examinations) and the implementation of a gymnastics program for the elderly which is carried out regularly every week on 12 February 2025. Data dissemination by implementing elderly posyandu with health examination methods and elderly gymnastics. Results: the elderly were active and enthusiastic in community service activities which were attended by 25 seniors, students and posyandu officers. The benefits of this activity help identify health problems of the elderly early and improve the health status of the elderly. This activity is expected to be carried out by Karta Dewa Village in a sustainable manner to improve the quality of life of the elderly.